Histochemical and Morphological Evaluation of the Conventional Versus Two Rapid Microwave Tissue Processing Techniques - Tobias Peter Pwajok Choji; Peterside Rinle Kumbish; Anthony Ajuluchukwu Ngokere; Samuel Ifedioranma Ogenyi; James O. Adisa; Boniface Nnamdi Duru; Comfort Danchal; Linus Doro Danjuma; Kaneng Pam Sha; Rifkatu Davou Pam (Archives of Current Research International, 2015)
Aims: To utilize the laboratory microwave as a processing instrument in place of the automatic tissue processor, to replace xylene with isopropanol in the clearing stage of tissue processing and check its effect on the chemical reactivity and tissue integrity, to establish a rapid method of tissue processing. Study Design: Fixation and grossing of tissues into triplicates. Processing, sectioning and histochemical demonstration of cells and extracellular components. Scoring of blocks and section, statistical evaluation of grades. Place and Duration of Study: The study was carried out at the central diagnostic Division, National Veterinary Research Institute, Vom, Jos, Nigeria, for 8 months between October, 2014 and May, 2015. Methodology: The Trachea, Lungs, Heart, Liver, Kidney, Stomach, Skin, Brain, and the Spleen were harvested from each of two apparently healthy rabbits after scientific ally sacrificing them and fixed in 10% buffered formalin for 3 days. They were grossed into triplicates, labeled and processed using the conventional, microwave without vacuum and microwave with vacuum respectively. They were sectioned and subjected to some histochemical methods as well as silver impregnation, graded and average scores subjected to one way Analysis of Variance (ANOVA) at 95% confidence interval. P-values less than 0.05 were considered statistically significant. Results: Reagents and time consumption were severely reduced in the microwave techniques when compared with the conventional method even as xylene was replaced with isopropanol, a cheaper and more user-friendly reagent than xylene. There was no statistically significant difference among the three techniques in terms of section preparation (P=.22), details of microscopic assessment/quality of tissue preservation (P=.74) and details of microscopic assessment/quality of staining (P=.90). Microscopic assessment/physical quality is also comparable among the three techniques (P=.74). Conclusion: A cheaper and faster method of tissue processing as presented in this work shows that histology results can be results in less than three hours of sample arrival. Xylene, with its deleterious effects on both the tissue and the laboratory personnel can now be eliminated from the processing schedule, with no negative effects of tissue morphology nor dye uptake. This was will encourage speed and accuracy in histopathology thereby improving patient care and management. Tissues processed using the microwave techniques can be assessed immunohistochemically since the microwave itself is used for antigen retrieval.